Early detection of anastomotic leakage after hand-sewn colorectal anastomoses - Albatanony, Ayman A.; Shahin, Mahmoud A.; Balpoush, Mohamed M. (International Surgery Journal, 2019)
Background: Colorectal anastomotic leakage is a serious complication leading to major postoperative morbidity and mortality. In the present study, author investigated the early detection of anastomotic leakage before its clinical presentation. Methods: This prospective study was including 80 consecutive patients with colorectal anastomoses using hand sewn technique. Patients follow-up was done to detect postoperative leak, study variables included hospital stay, wound infection, postoperative daily C-reactive protein, parameters of DULK-score and microbiological study of peritoneal fluid. Results: Clinically evident AL occurred in twelve patients (15%) and diagnosed postoperatively on median day 6. The median interval between appearance of the initial signs of clinical deterioration and the confirmation of AL was three days using DULK-score. C-reactive protein was significantly higher in patients with leakage with a cut-off value of 120 mg/l on 3rd postoperative day. Intraperitoneal bacterial colonization was significantly higher in patients with clinical evidence of AL (p value 0.012). Wound infection was significantly higher in anastomotic leakage group (p value 0.001). The hospital stay for the patients with anastomotic leakage was significantly longer than those without AL (p value 0.001). Conclusions: Routine application of DULK-score leads to diagnosis of AL three days earlier. C-reactive protein is a simple way to ensure a safe discharge from hospital after colorectal surgery.